Cytosolic re-localization and optimization of valine synthesis and catabolism enables inseased isobutanol production with the yeast Saccharomyces cerevisiae - Brat, Dawid (BioMed Central, 2012)
BACKGROUND: The branched chain alcohol isobutanol exhibits superior physicochemical properties as an alternative biofuel. The yeast Saccharomyces cerevisiae naturally produces low amounts of isobutanol as a by-product during fermentations, resulting from the catabolism of valine. As S. cerevisiae is widely used in industrial applications and can easily be modified by genetic engineering, this microorganism is a promising host for the fermentative production of higher amounts of isobutanol. RESULTS: Isobutanol production could be improved by re-locating the valine biosynthesis enzymes Ilv2, Ilv5 and Ilv3 from the mitochondrial matrix into the cytosol. To prevent the import of the three enzymes into yeast mitochondria, N-terminally shortened Ilv2, Ilv5 and Ilv3 versions were constructed lacking their mitochondrial targeting sequences. SDS-PAGE and immunofluorescence analyses confirmed expression and re-localization of the truncated enzymes. Growth tests or enzyme assays confirmed enzymatic activities. Isobutanol production was only increased in the absence of valine and the simultaneous blockage of the mitochondrial valine synthesis pathway. Isobutanol production could be even more enhanced after adapting the codon usage of the truncated valine biosynthesis genes to the codon usage of highly expressed glycolytic genes. Finally, a suitable ketoisovalerate decarboxylase, Aro10, and alcohol dehydrogenase, Adh2, were selected and overexpressed. The highest isobutanol titer was 0.63 g/L at a yield of nearly 15 mg per g glucose. CONCLUSION: A cytosolic isobutanol production pathway was successfully established in yeast by re-localization and optimization of mitochondrial valine synthesis enzymes together with overexpression of Aro10 decarboxylase and Adh2 alcohol dehydrogenase. Driving forces were generated by blocking competition with the mitochondrial valine pathway and by omitting valine from the fermentation medium. Additional deletion of pyruvate decarboxylase genes and engineering of co-factor imbalances should lead to even higher isobutanol production.